Synthesis of Methyl Ester Sulfonate from Crude Palm Oil Based on Aluminum Oxide Catalyst - Deli, Nur Asma; Hariani, Razita; Nasution, Rahma Sari (Journal of Engineering Science and Technology Management, 2025)
Surfactant is a surface active agent that reduces the surface tension of a medium, because it has the ability to combine parts between different phases such as air and water or phases that have different polarity such as oil and water. One of the vegetable oils that has great potential to be used as raw material for the manufacture of Methyl Ester Sulfonate (MES) is CPO. This Final Project aims to determine the manufacture of MES from CPO with Na2S2O5 as a sulfonation agent and understand the effect of Al2O3 (aluminum oxide) catalyst concentration on the characteristics of MES produced. The preparation of methyl esters was carried out by two-stage esterification and transesterification reactions using methanol as the alcohol source with H2SO4 as the acid catalyst and NaOH as the base catalyst. Sulfonation was carried out at temperature, ratio of methyl ester to Na2S2O5 1:1, Al2O3 catalyst concentration of 0.5%, 0.75%, 1%, 1.25%, and 1.5% and reaction time of 5 hours. The best results were obtained from the treatment of 0.75% Al2O3 catalyst concentration with the quality of MES produced having a yield of 88.27%, pH 7.51, acid number 4.48 mgKOH/g, density 887 kg/m3 and sulfonate absorbance value 0.155.